Administrative Procedural Relations between Justice and Judicial Oversight - Khandanyan, Rafik (Bulletin of Yerevan University C: Jurisprudence, 2024)
The article presents a deep and comprehensive analysis of the relationship between justice and judicial control within the framework of administrative judicial relations. First and foremost, the article addresses theoretical questions concerning the boundaries of justice and judicial control, as well as their methods of application. The main objective of the article is to demonstrate the role of justice and judicial control in the administrative proceedings of the Republic of Armenia and how they affect the legality of normative legal acts and the activities of administrative bodies. The work emphasizes that judicial control, as part of justice, is an important instrument in a legal state that ensures the legality of administrative decisions. It examines both direct and indirect forms of judicial control, describing their functional significance in administrative, criminal, and constitutional proceedings. Particular attention is given to judicial control over normative legal acts, noting that this process is crucial for ensuring legality in the realm of public administration. The article investigates how courts carry out the verification of the legality of normative legal acts and how this is reflected in the judicial practice of the Republic of Armenia. It also analyzes the interrelationship between administrative justice and procedures for imposing administrative liability, highlighting that administrative justice has its own characteristics that are significant in resolving disputes between administrative bodies and private individuals. The article further discusses the distinction between direct and indirect judicial control, identifying both abstract and concrete forms of control. Direct judicial control is viewed as the process of immediate verification of the legality of normative legal acts, while indirect control is exercised when the court is compelled to address the issue of legality in the context of a specific case. In the concluding section of the article, it is noted that justice and judicial control in administrative judicial relations have a clearly interconnected nature, which contributes to the development of a legal state and enhances the accountability of public authorities.